Essays on Two Implications of the Affordable Care Act (aca) - (:unkn) unknown (My University, 2016)
ESSAYS ON TWO IMPLICATIONS OF THE AFFORDABLE CARE ACT (ACA) by Esmaeil Salem The University of Wisconsin-Milwaukee, 2016 Under the Supervision of Professor Scott J. Adams The main objective of my dissertation is to investigate some of the causal effects of the Affordable Care Act (ACA) on U.S. healthcare system. After an overview about some of the new provisions enacted by the ACA and their components and timelines, effects of the ACA on immunization coverage for children under age of three and its impact on retention of the insureds receiving newly established rebates would be assessed. Chapter 2 evaluates changes in the up-to-date status of the nine vaccines recommended by the Advisory Committee on Immunization Practices (ACIP) for children aged 19 to 35 months following new provisions of the ACA that aimed to boost the coverage of the preventive services. By using a Difference-in-Difference identification strategy, I found that the ACA has significantly increased the number of up-to-date vaccines. In particular, it has boosted the up-to-date status for DTaP, Hepatitis A, and Varicella vaccines, especially for the states without universal or universal select programs prior to the ACA. While results show that families with lower income have utilized more benefits in the case of Varicella vaccine, parents with higher income and education have utilized more benefits in the case of the Hepatitis A vaccine. Also, the ACA has been more successful for Varicella vaccine in the states where non-religious exemptions were not permitted by law. Although the ACA might have been effective for these immunizations through eliminating the financial doubts for delays or refusals, since concerns about effectiveness and side effects of the vaccination have been reported as more important barriers, significant increases in the coverage should be seen as indirect information perceived by parents to address some of their non-price concerns. Chapter 3 investigates the changes in insureds’ retention rates once new rebate regulations under the ACA came into effect in 2011. By new provisions, if insurer does not spend at least 80% of the premiums collected from Individual Medical (IM) policies on claims and healthcare quality improvements, the left over should be returned to the insureds in form of the rebate. According to the literature, subjective value of the windfalls –like this rebate– could be different depending on how the recipient looks at the windfall. A rebate or returned wealth has a higher subjective value for the recipient than a bonus, and will more likely work as forced savings that convinces insured to stay with current insurer. Private insurance data used in the study shows that rebates have actually worked as a conventional rebate rather than a bonus, and have significantly discouraged insureds from lapsing, especially in the markets with fewer rivals. Also, larger amounts of the rebate show stronger impact on retention.
Keywords: Health Economics; Health Insurance; Immunization; Rebate